U-Pb Geochronology and Geochemistry of the Povungnituk Group of the Cape Smith Belt : Part of a Craton-Scale Circa 2.0 Ga Minto-Povungnituk Large Igneous Province, Northern Superior Craton - Kastek, N.; Ernst, R. E.; Cousens, B. L.; Kamo, S. L.; Bleeker, W.; Söderlund, U.; Baragar, W. R.A.; Sylvester, P. (Lithos, 2018)
Magmatism of the Povungnituk Group of the Cape Smith Belt, northern Superior craton, was formed in three stages: (i)early alkaline magmatism and associated carbonatites (undated), (ii) a main flood basalt sequence (Beauparlant Formation) (constrained between 2040 and 1991 Ma), and (iii) a late stage alkaline pulse (Cecilia Formation) (ca. 1959 Ma). We suggest that the main stage of magmatic activity (middle pulse) was of short duration. A new U–Pb baddeleyite age of 1998 ± 6 Ma is obtained from a dolerite sill intruding the uppermost section of the Beauparlant Formation. This age has regional significance because it matches the previously obtained 1998 ± 2 Ma age for the Watts Group (Purtuniq) ophiolite of the northern Cape Smith Belt and the 1998 ± 2 Ma U-Pb age of the Minto dykes intruding the craton to the south. These coeval units, along with additional units correlated on paleomagnetic grounds (Eskimo Formation), are interpreted to define a large igneous province (LIP), extending over an area of >400,000 km2, which we herein define as the Minto-Povungnituk LIP. Geochemical comparison between the Watts Group ophiolite, Minto dykes and the mafic Povungnituk Group shows significant differences allowing these data to be divided into two groups and domains within the LIP. A northern domain, comprising the Povungnituk and Watts groups, shows mixing between a depleted mantle source and a more enriched mantle plume-sourced melt. A southern domain comprising the Minto dykes and the paleomagnetically linked Eskimo Formation shows signs of an even more enriched source, while these magmas also show the effect of crustal contamination. Two distinct source mechanisms can be responsible for the observed geochemical differences between the two domains. First, a difference in lithospheric sources, where melting of different portions of Superior craton lithosphere caused the different melt signatures in the interior of the craton. In this case magmatism in the two domains is only related by having the same heat source ...